Stori Sydyn - Ros, Manon Steffan (Y Lolfa, 2012)
A title in the short and fast-paced series Quick Reads. A man returns to the town where he grew up, to start a new chapter in his life following his marriage breakdown. He has suffered from terrible nightmares for years - nightmares that become more regular after his move to the new flat. Intro – Clawr – Hawlfraint – Pennod 1 – Pennod 2 – Pennod 3 – Pennod 4 – Pennod 5 – Pennod 6 – Pennod 7 – Pennod 8 – Pennod 9 – Pennod 10 – Pennod 11 – Pennod 12 – Pennod 13 – Nodyn gan yr awdur – Y Lolfa.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books